Microstructure, Dielectric Properties and Bond Characteristics of Lithium Aluminosilicate Glass-Ceramics with Various Li/Na Molar Ratio - Minghan Li; Lingqi Kong; Wenzhi Wang; Yanping Ma; Hong Jiang (Crystals, 2023)
The advent of 5G technology presented new challenges regarding the high-frequency characteristics of electrical signals and their impact on the cover glass properties of electronic devices. This study aimed to analyze the effect of the Li/Na molar ratio on the dielectric and mechanical properties, as well as the structural characteristics, of lithium aluminosilicate glass-ceramics. Using the melting method, we prepared lithium aluminosilicate base glasses and subsequently crystallized them by adjusting the molar ratio. XRD and TEM analyses were employed to investigate the resultant structures and crystal formation in the five base glasses. It was observed that Li2Si2O5 and LiAlSi4O10 crystals precipitated, exhibiting varying degrees of crystallinity and crystal ratios. Through a comparison of dielectric properties before and after crystallization, it was found that the dielectric constants of the glass-ceramics were consistently reduced. This decrease can be attributed to the lower dielectric constants exhibited by both crystalline phases compared to the parent lithium aluminosilicate glasses. Furthermore, the presence of glass crystals effectively immobilized the alkali metal ions within the glass phase, impeding their movement under an electric field. Consequently, the dielectric loss value of the glass-ceramics decreased with the increasing amount of precipitated crystals. By carefully adjusting the composition and optimizing the crystallization process, we successfully produced lithium aluminosilicate glass-ceramics, demonstrating excellent mechanical and optical properties, coupled with low dielectric properties.